Pemanfaatan Teknologi Artificial Intelligence untuk Penguatan Kesehatan dan Pemulihan Ekonomi Nasional - Fitri Andri Astuti (Jurnal Sistem Cerdas, 2021)
Technological developments have been used to support health and economic systems in various countries. Especially during the COVID-19 pandemic, in the health sector, for example, starting from the process of identifying positive cases with chatbots, contact tracing, monitoring independent isolation, even monitoring social media for mental health can be done with the help of technology. This can help the government make policies and keep health workers in direct contact with patients, especially patients with mild symptoms, for patients with severe symptoms can be prioritized to be assisted by health workers. In the economic field, this pandemic has caused economic growth to decline, even in the third quarter of 2020 Indonesia experienced negative economic growth. The largest proportion of economic growth in Indonesia is household consumption, which is closely related to people's purchasing power. Artificial intelligence technology can be used to examine the level of public consumption. So that it helps the government in making policies on how to increase people's purchasing power. The use of this technology involves a variety of devices, online datasets, devices connected to the internet (IoT), and advances in the fields of machine learning, computer vision and natural language processing. This study aims to provide an overview of how artificial intelligence technology has great potential in strengthening the health system and restoring the national economy.